Directorate of Security Intelligence Based on Organization Structure and Work Procedure of the Regional Police - Sampara, Said; Qamar, Nurul; Syalman, Arri Abdi (CV. Social Politic Genius (SIGn), 2020)
This study aims to determine the effectiveness of the functions of the Directorate of Security Intelligence based on Organization Structure and Work Procedure of the South Sulawesi Regional Police. This research was conducted in South Sulawesi Province, with 92 respondents. Data analysis in this study uses a qualitative approach, which processes the output of the questionnaire, and is presented in the form of frequency tabulation (F) and percentage distribution (%). The results of this study show that the effectiveness of the function of the Directorate of Security Intelligence based on Organization Structure and Work Procedure of the South Sulawesi Regional Police, can be assessed from seven tasks, including: Directorate of Security Intelligence (Ditintelkam); Planning and Administration Subdivisions (Subbagrenmin); Analysis Divisions (Baganalisis); Administrative Services Section (Siyanmin); Intelligence Technology Section (Sitekintel); Coding Section (Sisandi); and Subdirectorate (Subdit). Research data from the overall function of the Directorate of Security Intelligence in South Sulawesi Regional Police shows less effective results. Seriousness is needed in increasing the effectiveness of the Directorate of Security Intelligence in South Sulawesi Regional Police to realize public order security.